Simultaneous presence of hypercoagulation and increased clot lysis time due to IL-1β, IL-6 and IL-8. (October 2018) - Bester, Janette; Matshailwe, Christina; Pretorius, Etheresia
Highlights: Investigating the effects of individual circulating inflammagens, to better understand the role that each play in the expression of disease. Results showed that IL-1β; IL-6 and IL-8 causes hypercoagulation and also hyperfibrinolysis. Both clot lysis time and maximum rate of lysis are decreased with the addition of the interleukins. A Final conclusion made is that these (separate) interleukins result in hypercoagulation, with an enhanced lyses and disheveled fibrin clot ultrastructure. Abstract: Circulating cytokines, and particularly the interleukin (IL)-family are known to play an important role in inflammation. These molecules circulate in the blood and therefore have a direct effect on the plasma molecules and the formed elements like the erythrocytes and platelets. Aberrant coagulation (hypercoagulation or blood clots that form too easily) and clot lyses (hypofibrinolysis, where clots do not dissolve properly, with an abnormally low rate of clot lysis time), are usually the hallmarks of many inflammatory conditions. However, the mechanism by which cross-linking augments clot stiffness remains undetermined. IL-1β; IL-6 and IL-8 has been found to be involved in most chronic and acute inflammatory diseases. In the present study, we investigate clot structure of healthy blood, with the addition of these 3 interleukins, to determine the individual effects at concentrations that mimic low-grade, chronic inflammation. Previous studies showed that clot rheological behavior is regulated by at least the following three factors, fibrinogen concentration, fibrin network architecture and FXIIIa-induced ligation. We investigated clot formation and lysis using thromboelastography (TEG), before and after exposure, and created clots by adding thrombin to whole blood. This allowed us to look at extensive fibrin fiber formation and their interactions with particularly the erythrocytes, using scanning electron microscopy (SEM). Our results showed that IL-1β; IL-6 and IL-8 causes hypercoagulation and results in a disheveled fibrin clot, with trapped RBCs. IL-8 showed eryptosis (a type of apoptosis in erythrocytes). Our lysis results showed that both clot lysis time and maximum rate of lysis are decreased, with the addition of the interleukins. This is a novel finding and the observations reported in this paper, therefore points to the importance of looking at the effects of individual circulating inflammagens, to better understand the role that each play in the expression of disease. These methods can be used for an individualized patient-orientated approach in healthcare to track blood viscosity in conditions with acute and chronic inflammation.